Perencanaan Mitigasi Risiko Berbasis Event Tree Analysis untuk Meningkatkan Keandalan PLTGU - Sastya Adzani Syahbania; I Ketut Gunarta (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2026)
Repeated failures of critical equipment at power generation facilities can significantly disrupt operations and reduce system availability. In 2023, PT X's Block 1 Unit A Combined Cycle Power Plant recorded its lowest Equivalent Availability Factor (EAF) of 84.95% due to repeated failures of several critical components. Previous studies have identified these equipment failures and analyzed their reliability levels. This study aims to develop mitigation scenarios to reduce operational risks using Event Tree Analysis (ETA). ETA uses failure probabilities from previous reliability assessments as initiating events to model potential event sequences and evaluate their consequences. The results show that each tool generates between 4 and 16 scenario pathways, depending on the number of mitigation programs. All proposed mitigation scenarios successfully reduced the overall risk level to “Low” across all seven critical pieces of equipment. This study concludes that ETA provides an effective way to systematically organize mitigation efforts based on failure probability and consequence analysis. The contribution of this study is the development of a scenario-based mitigation framework using ETA to support decision-making and enhance operational reliability at combined-cycle power plants.